Relationship between Knowledge and Attitude toward BSE Behavior for Early Breast Cancer Detection among Atma Jaya Hospital Nurses - Zita Arieselia; Kurniawan, Sandy Vitria; Lonah; Linawati Hananta; Freggy Spicano Joprang; Edward Surjono; Jonny Setiawan; Andrew Liputra; Jennifer (Journal of Urban Health Research, 2025)
Introduction : Breast cancer is a frequently occurring type of cancer in Indonesia, with symptoms of rapid and invasive growth of abnormal cells. Deaths due to this cancer can be reduced by avoiding risk factors and early detection, such as through breast self-examination (BSE). Assessing knowledge, attitudes, and behavior regarding BSE is important for early detection, especially for nurses as health workers. This study assessed the relationship between knowledge and attitudes towards BSE behavior among Atma Jaya Hospital nurses.  Methods: This is an analytical observational study employing a cross-sectional design, involving 105 samples selected through purposive sampling according to established inclusion and exclusion criteria. The variables in this study include knowledge, attitude, and behavior regarding breast self-examination (BSE). Data were collected through the distribution of questionnaires to respondents and will be statistically analyzed using the Chi-Square test (x2) with a significance level (a) = 5%, and the analysis will be conducted using STATA software. Results: Based on the data analysis, there is no correlation between knowledge and attitude toward the practice of breast self-examination (BSE), with p-values of 0.623 and 0.994. Conclusion: There is no significant relationship between Knowledge and Attitude towards BSE Behavior. Keywords:  BSE Attitude - BSE Behavior - BSE Knowledge